Bipolar membrane electrodialysis for energetically competitive ammonium removal and dissolved ammonia production. (20th June 2020) - van Linden, Niels; Bandinu, Giacomo L.; Vermaas, David A.; Spanjers, Henri; van Lier, Jules B.
Abstract: Removal of ammoniacal nitrogen from residual waters traditionally relies on energy-consuming biochemical processes, while more novel alternative strategies focus on the recovery of total ammoniacal nitrogen for the production of fertilisers or the generation of energy. The recovery of total ammoniacal nitrogen as gaseous ammonia is more effective at high ammonia concentrations in the liquid feed. Typically, chemicals are added to increase the solution pH, while bipolar membrane electrodialysis can be used to convert salt solutions to acid and base solutions by using only electricity. In this study, we used bipolar membrane electrodialysis to remove ammonium from water and to simultaneously produce concentrated dissolved ammonia, without using chemicals. The energy consumption and current efficiency to transport ammonium from the diluate (the feed water) were assessed throughout sequencing batch experiments. The total ammoniacal nitrogen removal efficiency for bipolar membrane electrodialysis ranged between 85 and 91% and the energy consumption was stable at 19 MJ·kg-N −1, taking both electrochemical and pumping energy into account. The base pH increased from 7.8 to 9.8 and thetotal ammoniacal nitrogen concentration increased from 1.5 to 7.3 g L −1, corresponding to a final ammonia concentration of 4.5 g L −1 in the base. Leakage of hydroxide, diffusion of dissolved ammonia and ionic species from the base to the diluate all contributed to a loss in current efficiency. Due to the increase in operational run time and concentration gradients throughout the sequencing batch experiments, the current efficiency decreased from 69 to 54%. We showed that bipolar membrane electrodialysis can effectively be used to simultaneously remove ammonium from water and produce concentrated dissolved ammonia while avoiding the use of chemicals. Moreover, the energy consumption was competitive with that of the combination of electrodialysis and the addition of chemicals (22 MJ·kg-N −1 ). Highlights: Ammonium (NH4 + ) removal by bipolar membrane electrodialysis ranged 85–91%. Final base pH and ammonia (NH3 ) concentration were 9.8 and 4.5 g L −1, respectively. Energy consumption for NH4 + removal and dissolved NH3 production was 19 MJ·kg-N −1 . Leakage and diffusion processes decreased the NH4 + current efficiency from 69 to 54%. Energy consumption was competitive to electrodialysis + the addition of chemicals.